The relay race to infinity developments in mathematics from Euclid to Fermat - Holton, Derek Allan 1941-; Stillwell, John 1942- (World Scientific, 2025)
"The book is not solely based on maths and the mathematicians who made important discoveries; maths and mathematicians are set against the world during their times; Maths has often been taught as a series of techniques. The human side of the topic has gotten lost. We are trying to show mathematicians as people with their own daily problems that they have to cope with. For example, Pascal and the very bad migraines that he suffered for virtually all of his life; In an effort to add a more personal side to their teaching, the various episodes in the book should enable teachers to provide their students with interesting stories. These will make the subject more compelling and will help them to remember aspects of the syllabus; We strongly believe that this approach is not only more fun, but also more enlightening; avoiding the sin of confronting students with concepts in modern form without any clues about their origins or motivation."
Keywords: Mathematicians; Mathematics / Miscellanea; Euclid; Liu, Hui / active 3rd century-4th century; Fibonacci, Leonardo / approximately 1170-approximately 1240; Fermat, Pierre de / 1601-1665